PENGARUH PROMOSI, KUALITAS PRODUK DAN HARGA TIKET TERHADAP KEPUASAN PENGUNJUNG WISATA EDUCATION GONDANG OUTBOND (WEGO) LAMONGAN - Nawari Nawari; Nur Lailatul Mahfudho (Fakultas Ekonomi Universitas Islam Darul Ulum Lamongan, 2019)
The era of globalization has demanded changes in all fields. One of them is the field of tourism marketing. The purpose of this study was to examine the effect of promotion, product quality and ticket prices on tourist visitor satisfaction. This research was conducted at Gondang Outbond Education Tourism, respondents used 60 visitors of the gondang outbond education tour using SPSS. The results show that product quality and ticket prices have a positive and significant influence on customer satisfaction. while promotion has a negative effect on consumer satisfaction. Product quality and ticket prices are the most important variables in influencing customer satisfaction.